2017
DOI: 10.1155/2017/5836397
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Predisposing Factors of Difficult Airway during Induction of General Anaesthesia

Abstract: Objective To assess magnitude and predisposing factors of difficult airway during induction of general anaesthesia. Methods Hospital based cross sectional study carried out to determine the incidence of difficult mask ventilation, difficult laryngoscopy (Cormack and Lehane III and IV), difficult intubation (IDS ≥ 5), and failed intubation. The association between each predisposing factor and airway parameters with components of difficult airway is investigated with binary logistic regression. Sensitivity, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…There were 218 test comparisons from 92 studies for difficult laryngoscopy, 72 comparisons from 50 studies for difficult intubation, 18 comparisons from seven studies for difficult facemask ventilation and two comparisons from two studies for failed intubation. Overall, the median (IQR [range]) number of participants per study, proportion of female participants, age and body mass index were 380 (200–662 [14–103,728]), 53% (44–64% [0–100%]), 45 (39–52 ) years and 27.3 (24.8–30.0 ) kg.m −2 , respectively. All studies except four performed airway management in operating theatres, two in the pre‐hospital setting and the others occurred in emergency rooms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 218 test comparisons from 92 studies for difficult laryngoscopy, 72 comparisons from 50 studies for difficult intubation, 18 comparisons from seven studies for difficult facemask ventilation and two comparisons from two studies for failed intubation. Overall, the median (IQR [range]) number of participants per study, proportion of female participants, age and body mass index were 380 (200–662 [14–103,728]), 53% (44–64% [0–100%]), 45 (39–52 ) years and 27.3 (24.8–30.0 ) kg.m −2 , respectively. All studies except four performed airway management in operating theatres, two in the pre‐hospital setting and the others occurred in emergency rooms.…”
Section: Resultsmentioning
confidence: 99%
“…We identified further studies from references of retrieved articles and used citation tracking in Science Citation Index. The search was updated in March 2018 but we have not incorporated the results from 27 studies in this review.…”
Section: Methodsmentioning
confidence: 99%
“…Difficult air way and intubation risk is more profound in pregnancy and obesity almost double risk when it is compared with other normal patients as it is supported by the systematic review [ 10 ]∗. The risk is high in pregnancy because of pregnancy related physiologic and anatomic changes such as large breast, edematous air way and frequent hypoxia, which is due to limited diaphragmatic excursion due to gravid uterus, high oxygen consumption and high risk of aspiration to have standard laryngoscopy by repeated attempts.…”
Section: Discussionmentioning
confidence: 92%
“…A study conducted in Gonder surgical hospital showed the most important predominant risk factors of difficulty airway are Mallampati classes III & IV, mouth opening < 30 mm, JSD grade C, attempt> 3, and ineffective alternative technique [13]. Generally, different parameters for the prediction of difficult airways have been studied.…”
Section: Discussionmentioning
confidence: 99%